The causes and consequences of delayed/abandoned cross-border merger & acquisition transactions: A cross-case analysis in the dynamic industries. Issue 6 (3rd October 2016) - Reddy, K.S.; Xie, En; Huang, Yuanyuan
Abstract : Purpose: Drawing attention to the significant number of unsuccessful (abandoned) cross-border merger and acquisition (M&A) transactions in recent years, the purpose of this paper is to analyze three litigated cross-border inbound acquisitions that associated with an emerging economy – India, such as Vodafone-Hutchison and Bharti Airtel-MTN deals in the telecommunications industry, and Vedanta-Cairn India deal in the oil and gas exploration industry. The study intends to explore how do institutional and political environments in the host country affect the completion likelihood of cross-border acquisition negotiations. Design/methodology/approach: Nested within the interdisciplinary framework, the study adopts a legitimate method in qualitative research, that is, case study method, and performs a unit of analysis and cross-case analysis of sample cases. Findings: The critical analysis suggests that government officials' erratic nature and ruling political party intervention have detrimental effects on the success of Indian-hosted cross-border deals with higher bid value, listed target firm, cash payment, and stronger government control in the target industry. The findings emerge from the cross-case analysis of sample cases contribute to the Lucas paradox – why does not capital flow from rich to poor countries and interdisciplinary M&A literature on the completion likelihood of international takeovers. Practical implications: The findings have several implications for multinational managers who typically involve in cross-border negotiations. The causes and consequences of sample cases would help develop economy firms who intend to invest in emerging economies. The study also offers some implications of M&A for telecommunications and extractive industries. Originality/value: Although a huge amount of extant research investigates why M&A fail to create value to the shareholders during the public announcement and post-merger stages, there is a significant dearth of research on the causes and consequences of delayed or abandoned national and international deals. The paper fills this knowledge gap by discussing an in-depth cross-case analysis of Indian-hosted cross-border acquisitions.